Estimación de emisiones de metano producidas por gestión de estiércol proveniente de sistemas de producción de bovinos de leche en Majes – Arequipa - Juan E Reategui Ordoñez (2017)
The information collected from 24 Majes Irrigation farms was processed, analyzed, and differentiated by its production system; the information came from the handling characteristics, diet composition and animal production indicators. The aim was to estimate methane emissions produced by handling manure by means of the equations provided by the Intergovernmental Panel on Climate Change (IPCC) by the methodology of Level 2. The analysis was performed by a completely randomized design with a probability of 95%, using SAS V9.0 program. It was found that the rate of excretion, digestibility and gross energy from handling manure by the intensive system was 5,78 ± 0,78; 70,45 ± 2,30 and 361,41 ± 42,05 MJ/day respectively, indicators led to a CH4 emission of 0,99 ± 0,13 kg CH4/cow/year. Handling manure under conditions of the Majes Irrigation varies significantly (P <0.05), influenced by the production system, 0,99 ± 0,13 kg CH4/animal/year and 1,16 ± 0,15 kg CH4/animal/year; for intensive and semi-intensive system, respectively. These results have been regulated by the quality of the diet, mainly in terms of crude protein and digestibility of the diet would have expected the growth of methanogenic bacteria in the manure, and the disposal of excreta in each system, under Majes irrigation conditions.